The Influence of Materialism on Ecotourism Attitudes and Behaviors - Lu, A.; Gursoy, D; Chiappa, G.; Chiappa, G. (SAGE Publications, 2015)
This study examined the relationships among materialism, ecotourism attitude, ecotourism interest, ecotourism intention, and willingness to pay a premium for ecotourism utilizing a model that was developed based on the literature. Data for this study were collected from 2,352 Italian travelers and proposed hypotheses were tested using a structural equation modeling approach. Findings indicated that individuals’ materialistic value has negative relationships with their ecotourism attitude, ecotourism interest, ecotourism intention, and willingness to pay a premium for ecotourism products and services. Findings also suggested that individuals’ ecotourism attitude would positively influence ecotourism intention, ecotourism interest, and willingness to pay a premium for ecotourism products and services.